Influence of Sodium Alginate on Hypoglycemic Activity of Metformin Hydrochloride in the Microspheres Obtained by the Spray Drying - Marta Szekalska; Magdalena Wróblewska; Katarzyna Sosnowska; Katarzyna Winnicka (International Journal of Polymer Science)
Alginate microspheres with metformin hydrochloride were prepared by the spray drying method in order to improve residence time of drug in the stomach. Nine formulations (F1–F9) with various drug : polymer ratio (1 : 2, 1 : 1, and 2 : 1) and different sodium alginate concentration (1%, 2%, and 3%) were evaluated for size, morphology, drug loading, Zeta potential, and swelling degree. In vitro drug release, mathematical release profile, and physical state of microspheres were also evaluated. Optimal formulation characterized by the highest drug loading was formulation F6 (drug : polymer ratio 2 : 1 and 2% alginate solution). Based on glucose uptake in Saccharomyces cerevisiae cells and α-amylase inhibition tests, it could be concluded that alginate microspheres enhance hypoglycemic activity of metformin hydrochloride evaluated in vitro. Designed microspheres are promising as alternative, multicompartment dosage form for metformin hydrochloride delivery.